2005
DOI: 10.1002/mds.20635
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between eye symptoms and blepharospasm: A multicenter case–control study

Abstract: Although patients with primary blepharospasm (BSP) commonly report experiencing ocular symptoms before the onset of orbicular spasms, the precise frequency and pathogenic role of this subjective ocular discomfort are poorly understood. We conducted a multicenter case-control study to investigate symptoms related to disorders of the anterior segment of the eye, administering a questionnaire to 165 patients with BSP and 180 age- and gender-matched control patients with hemifacial spasm. On a validation sample, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 26 publications
(44 reference statements)
1
53
0
4
Order By: Relevance
“…Moreover, Wen-Juh Hwang reported that only 11% of the patients spontaneously complained of photophobia, but upon questioning, 97% of the patients had photophobia [3]. Eye symptoms associated with PBS result from eye diseases and may be involved in the pathogenesis of PBS [12]. The first-degree relatives of blepharospasm patients more frequently had eye symptoms such as dry eyes and gravel and burning sensations [13].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Wen-Juh Hwang reported that only 11% of the patients spontaneously complained of photophobia, but upon questioning, 97% of the patients had photophobia [3]. Eye symptoms associated with PBS result from eye diseases and may be involved in the pathogenesis of PBS [12]. The first-degree relatives of blepharospasm patients more frequently had eye symptoms such as dry eyes and gravel and burning sensations [13].…”
Section: Discussionmentioning
confidence: 99%
“…18 Blink reflex recovery cycle. The blink reflex recovery cycle was studied, according to the experimental procedure reported in previous studies, by delivering electrical shocks to the supraorbital nerve through silver chloride disc surface electrodes.…”
mentioning
confidence: 99%
“…The neurologist then 1 Integrative Medicine Centre, Fairhope, AL. 2 recommended a neuro-ophthalmologist for another opinion. The neuro-ophthalmologist's diagnosis was ''benign essential blepharospasm'' 4,5 and Klonopin was prescribed.…”
Section: Case Historymentioning
confidence: 99%
“…It is a relatively rare disease occurring in only about 1 in every 20,000 adults in the United States. 2 The first record of blepharospasm and lower facial spasm was documented in the 16th century in a painting titled De Gaper. At that time, and for several ensuing centuries, patients with such spasms were regarded as being mentally unstable and often were institutionalized in insane asylums.…”
Section: Introductionmentioning
confidence: 99%